We are told that f(x) = x + 2. We want to find
.
Squaring f(x) on one side means we square x + 2 on the other.
So,
f(x) = x + 2
(f(x))² = (x + 2)²
= (x + 2)(x + 2)
We can use FOIL to square x + 2. The first terms multiply to x², the outside terms to 2x, the inside terms to 2x and the last terms to 4.
= x² + 2x + 2x + 4
= x² + 4x + 4
So [f(x)]² = x² + 4x + 4
Answer:
she worked 17 hours
Step-by-step explanation:
first you subtract 256-40
then you get 216 and divide by 8
then you get 27 as an answer
Answer:
D
Step-by-step explanation: